Acute HIV infection with presentations mimicking acalculous cholecystitis: A case report. Issue 28 (16th July 2021) - Liu, Wang-Da; Cheng, Chih-Ning; Lin, Ya-Ting; Kuo, Ching-Hua; Ho, Shu-Yuan; Hung, Chien-Ching
Abstract: Rationale: Acute retroviral syndrome is the symptomatic presentation of acute human immunodeficiency virus (HIV) infection, which often manifests as a self-limited infectious mononucleosis-like syndrome and occurs 2 to 6 weeks after exposure to HIV. Atypical manifestations including hepatitis, meningitis, or hemophagocytic lymphohistiocytosis have been reported. However, manifestations of acute acalculous cholecystitis during acute HIV infection are rarely reported. Patient concerns: A 30-year-old man with nausea and loose stools, followed by fever and abdominal pain at the right upper quadrant for 10 days. Diagnosis: Acute retroviral syndrome, complicated with acute acalculous cholecystitis. Interventions: Percutaneous transhepatic gallbladder drainage was performed and treatment with co-formulated bictegravir/emtricitabine/tenofovir alafenamide was initiated upon HIV diagnosis. Outcomes: The patient's symptoms improved after the drainage. The levels of liver enzyme including aspartate transaminase alanine aminotransferase decreased to a level within normal limits 1 month after initiation of antiretroviral therapy. Conclusion: Acalculous cholecystitis in combination with acute hepatitis could be manifestations of acute HIV infection. For individuals at risk of acquiring HIV infection who present with manifestations of acute acalculous cholecystitis, HIV testing should be considered. Abstract : Supplemental Digital Content is available in the text